2003
DOI: 10.1051/0004-6361:20030679
|View full text |Cite
|
Sign up to set email alerts
|

The Hamburg/RASS Catalogue of optical identifications

Abstract: We present the Hamburg/RASS Catalogue (HRC) of optical identifications of X-ray sources at high-galactic latitude. The HRC includes all X-ray sources from the ROSAT Bright Source Catalogue (RASS-BSC) with galactic latitude |b| ≥ 30 • and declination δ ≥ 0 • . In this part of the sky covering ∼10 000 deg 2 the RASS-BSC contains 5341 X-ray sources. For the optical identification we used blue Schmidt prism and direct plates taken for the northern hemisphere Hamburg Quasar Survey (HQS) which are now available in d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
119
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(132 citation statements)
references
References 42 publications
12
119
0
1
Order By: Relevance
“…The very soft X-ray spectrum (HR1 = −1.0) clearly points towards the white dwarf PG 1232+238 as the counterpart, consistent with the identification by Zickgraf et al (2003).…”
Section: Sdss Spectrasupporting
confidence: 82%
See 3 more Smart Citations
“…The very soft X-ray spectrum (HR1 = −1.0) clearly points towards the white dwarf PG 1232+238 as the counterpart, consistent with the identification by Zickgraf et al (2003).…”
Section: Sdss Spectrasupporting
confidence: 82%
“…38a: classified as QSO in Zickgraf et al (2003); too faint on Sonneberg plates for variability assessment. The SDSS-III spectrum classifies it as broadline QSO at z = 0.5471.…”
Section: Sdss Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…It is listed in the ROSAT all-sky survey (Schwope et al 2000) and identified in the Hamburg/RASS bright source identification catalogue (Zickgraf et al 2003). A study of the X-ray selected Seyfert galaxies by Vaughan et al (2001) listed HD 123351 in their Galactic sample with a Galactic column density of 1.25 × 10 20 cm −2 .…”
Section: Introductionmentioning
confidence: 99%